PENGARUH PENGERJAAN AKHIR TERHADAP STABILITAS DlMENSI KAYU - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
This study was designed to determine the ability of six commercial exterior finishes (2 clear coats and 4 opaque coats) in protecting wood from dimensional changes. Two wood species, jabon (Anthocephalus cadamba Miq.) and mangium (Acacia mangium Willd.) were used in this study. Samples were seasoned to air-dry condition (moisture content of 15-17%)and then divided into groups on the basis of treatments and groin orientation (radial and tangential). Application of each exterior finish was undertaken according to procedures suggested by the finish manufacturer. The effectiveness of treatments to dimensionally stabilize wood was determined by measurements of wood swelling within 72-hours immersion and calculation of a.:d-.swelling efficiency (ASE). Results of observations made to this stage showed that the effect of finishing on wood dimensional stability varied according to wood species, grain orientation and type of finish coat. Finishing had a greater dimensional stabilizing effect on Jabon than mangium. Reduction of swelling due to finishing was greater in tangential compared to radial boards. The use of clear coats significantly gave less protection on wood stability than that of opaque coats. Anti-swelling efficiency of all treatments markedly decreased with increasing period of immersion.